Penerapan Prinsip Fiduciary Duty dalam Kejahatan Perdagangan Orang dalam Insider Trading: Studi Kasus di Indonesia dan Amerika (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
Capital Market in general terms is defined as a business sector of trading securities such as shares, stock certificates, and bonds or securities in general. In practice, not all information can be accessed simultaneously by all people, so this becomes a problem in the capital market or can be said to be a crime, Crime in the capital market is increasingly rampant, one of which is insider trading or insider trading which is a form of crime and violation included in the capital market, Regulations regarding insider trading in Indonesia are regulated in Law Number 8 of 1995 in conjunction with Law No. 4 of 2023. Capital market crimes in the form of insider trading that occur both in Indonesia and in developed countries such as the United States both have detrimental effects on the public as investors, but the accountability carried out is different for insider trading perpetrators in each of these countries, therefore it is necessary to review how the legal regulations of insider trading in Indonesia and the United States relate to these two cases.